Antimicrobial and Antibiofilm Activity of 4-Benzylidene-2-methyl-oxazoline-5-one against Pathogen Bacteria - Zahra Mortazavi; Mohamad Reza Islami; Moj Khaleghi (Journal of Genetic Resources)
One of the major challenges in healthcare is the rise of antibiotic resistance, where bacteria have developed resistance to a wide range of commonly available antibiotics. These resilient bacteria pose a significant threat to public health, leading to severe illnesses and creating a substantial challenge for treatment. Therefore, the discovery of new antimicrobial agents is crucial in controlling the spread of infections caused by drug-resistant bacteria. This study focuses on the synthesis of oxazoline and investigates the antimicrobial and anti-biofilm properties of this compound named 4-benzylidene-2-methyl-oxazoline-5-one. The structure of the oxazoline compound was precisely characterized by 1H NMR, 13C NMR, and FT-IR. The antibacterial activity was assessed on S. aureus using the agar-well diffusion while the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values were determined to identify the concentration ranges with significant inhibitory effects. S. aureus is one of the most noticeable microorganisms in medical and clinical sciences, especially nosocomial infections. Additionally, the study evaluated the compound's impact on biofilm formation and the expression of the icaA gene. The results from the MIC and MBC testing demonstrated that the compound exhibits both bacteriostatic and bactericidal effects on both Gram-positive and Gram-negative bacteria, as well as yeast. Furthermore, the presence of this antibacterial compound led to a reduction in icaA gene expression. 4-Benzylidene-2-methyl-oxazoline-5-one displayed significant antimicrobial activity and hindered biofilm formation. Moreover, it was observed that 4-benzylidene-2-methyl-oxazoline-5-one induced cell death through its toxic effects on MCF-7 cells. When it was tested at concentrations of 0.01, 0.1, and 1 mg/ml this compound exhibited cytotoxic effects and significantly decreased cell viability.